2007
DOI: 10.1007/s00415-006-0383-9
|View full text |Cite
|
Sign up to set email alerts
|

Regional patterns of cerebral glucose metabolism in spinocerebellar ataxia type 2, 3 and 6

Abstract: The purpose of this study was to investigate the regional patterns of cerebral metabolic deficits by voxel-based FDGPET analysis in patients with distinct spinocerebellar ataxia (SCA) genotypes, including SCA type 2 (SCA2), SCA3, and SCA6. Nine patients with SCA2, 12 with SCA3, seven with SCA6, and 23 healthy control subjects were recruited. The clinical severity of the patients' cerebellar ataxia was evaluated according to the International Cooperative Ataxia Rating Scale. The brain glucose metabolism was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 38 publications
4
37
1
Order By: Relevance
“…Interestingly, we found the blood glucose was significantly reduced in SCA17 transgenic mice at 5 weeks of age. Although no report pointed out that the blood glucose was affected in SCA patients, the hypometabolism phenomenon was observed by positron emission tomography (PET) with 2-[fluorine18]-fluoro-2-deoxy-D-glucose in the cerebellum of SCA patients [32], indicating that the dysfunction of energy metabolism might be another pathology of SCAs. However, at this moment, we do not know whether our SCA17 mice have a defect in energy metabolism or whether the trehalose treatment has any effect on the hypometabolism phenomenon of the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found the blood glucose was significantly reduced in SCA17 transgenic mice at 5 weeks of age. Although no report pointed out that the blood glucose was affected in SCA patients, the hypometabolism phenomenon was observed by positron emission tomography (PET) with 2-[fluorine18]-fluoro-2-deoxy-D-glucose in the cerebellum of SCA patients [32], indicating that the dysfunction of energy metabolism might be another pathology of SCAs. However, at this moment, we do not know whether our SCA17 mice have a defect in energy metabolism or whether the trehalose treatment has any effect on the hypometabolism phenomenon of the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…On the structural level, a cerebellar atrophy was demonstrated in conventional structural neuroimaging in SCA17 [7,17] and also in other SCA genotypes, such as SCA1, 2, and 3 [18]. On the metabolic level, in SCA1, 2, 3, and 6 cerebellar glucose metabolic deficits were reported using fluorodeoxyglucose positron emission tomography (FDG PET) [19,20]. The basal ganglia, playing a fundamental role in the extrapyramidal motor system, seem to be involved in the pathological process in SCA17.…”
Section: Regression Analysis Between Gmv Degeneration and Motor Scalementioning
confidence: 96%
“…Soong et al [55] found that glucose metabolism rates were significantly lower not only in the cerebellar hemispheres, but also in the brain stem, basal ganglia, and frontal, temporal, and occipital cerebral cortices, while Honjo et al [56] found that regional cerebral blood flow was decreased only in the cerebellar vermis and hemispheres in SCA6 patients. Recently, statistical parametric mapping demonstrated that brain metabolism and perfusion were diminished in the cerebellum and the prefrontal cortices in SCA6 [57, 58]. Kawai et al [57] revealed that neuropsychological test scores in SCA6 patients were significantly correlated with a decrease in prefrontal perfusion, and suggested that the cognitive dysfunctions in SCA6 patients may result from prefrontal dysfunction, based on the functional deactivation of the cerebello-ponto-thalamo-cerebral pathways.…”
Section: Spinocerebellar Ataxia Typementioning
confidence: 99%